Damage-less observation of polymers by electron dose control in scanning electron microscope. (27th January 2021) - Hashimoto, Yoichiro; Shigeto, Kunji; Komatsuzaki, Ryo; Saito, Tsutomu; Sekiguchi, Takashi
Abstract: Methodology for quantitative evaluation of electron radiation damage and calculation of tolerable electron dose was developed to achieve damage-less scanning electron microscope (SEM) observation of beam-sensitive polymer film. The radiation damage is typically evaluated with visual impressions of SEM images; however, this method may be unreliable because observer's subjectivity may affect the results. Evaluation with quantitative value is crucial to improve reliability. In this study, the radiation damage was evaluated by using normalized correlative coefficient ( RNCC ) between an initial frame and latter frames of the multiple SEM images that were taken consecutively. Tolerable dose was obtained by defining a threshold point of RNCC where rapid reduction of RNCC started. A SEM image with less damage and acceptable signal-to-noise ratio was obtained by integrating the images from the initial frame to the tolerable frame.